Does Javanese have Inflectional Phrase? - Agus Subiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
Abstract        In generative grammar, especially in the X-bar theory, all syntactic constructions are claimed to be endocentric.  This principle enforces a sentence or a clause to be treated as an inflectional phrase, with the inflectional category as the head. This principle has been attested for many languages and it has become a general rule. However, some languages like Javanese may behave differently from languages having the inflection system like English. This paper aims to discuss whether Javanese has Inflectional phrase or not. The data used in this study was taken from a Javanese magazine Panjebar Semangat, collected using an observation technique. The result of the analysis shows that Javanese lexicons expressing tense, aspect, and modals belong to inflections and they have the maximal projection as Inflectional Phrase.  Keywords: inflectional phrase, Javanese, X-bar theory